Faktor Ekonomi Makro dan Mikro yang Mempengaruhi Profitabilitas Bank Perkreditan Rakyat Syariah di Provinsi Banten - Salviana; IGN Oka Widana (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to analyze and examine macro and micro economic factors that influence the profitability of Bank Perkreditan Rakyat Syariah in Banten Province consisting of Banten Regional gross domestic product, Banten Regional inflation, bank size, capital adequacy ratio and non-performing financing. This study uses quarterly time series data from 2020 to 2023 with a sample of 16 quarters. The model used is a panel data regression model using EViews 12 software. The results of the study show that Banten Regional gross domestic product, Banten Regional inflation and bank size partially have no effect on the return on assets of Bank Perkreditan Rakyat Syariah in Banten Province. While capital adiquacy ratio and non-performing financing partially affect the return on assets of Bank Perkreditan Rakyat Syariah in Banten Province. Simultaneously, the results of this study are all independent variables, namely: Banten Regional gross domestic produc, Banten Regional inflation, bank size, capital adequacy ratio and non-performing financing together have a significant effect on the dependent variable, namely return on assets of Bank Perkreditan Rakyat Syariah in Banten Province.